Pohanský idol z Kouřimi, Česká republika Poganski idol s Kouřima, Češka republika - Nad’a Profantová (Studia Mythologica Slavica, 2012)
The paper considers the findings about the archaeologically detectable pre-Christian manifestation in the hill-fort of Kouřim/Kurim in the 10th century written report in Middle Bohemia. The small non-complete stone »idol«(post), 17 cm in hight, is published in the article. It is decorated in two lines: The upper brings 5 faces (human masks), the lower one shows two smaller complete faces with headbands, originally it consisted of 6. The stone idol was found before the year 1998 near the third wall (fortification line) – not far from the cultic place near the spring »U Libuše« (fig. 1). It is probably a pagan idol from the 9th and 1st half of the 10th century with symbolic meaning. The upper faces could symbolise the world of Gods, the lower one the world of people or world of rules. This idol is unique evidence about the developed slavic paganism in Bohemia du ring the 9th–10th century.